Sustainable initiatives in marginal rural areas of Serbia: A case study of Dimitrovgrad municipality - Rodriguez, Juan-Pablo (Applied Studies in Agribusiness and Commerce, 2011)
his paper is based on a 2009 case study research on the role and impacts of rural initiatives in Dimitrovgrad, South-eastern Serbia region. This area is of interest, because of local efforts to conserve autochthonous livestock breeds,andtheworkofsmallholdersandindependent professionals involved farming and rural tourism activities. The research used participant visits to initiative places, drawing on farm visits, meetings with stakeholders and analysis of secondary information. The study highlights that local organizations are running without link to initiatives.Although, Serbia country has well structured rural developments programs, those still are harmonising.Thus, throughActor-Network approach is suggested which turn around a farm manager. This may represent to all stakeholders with initiatives (on-farm and non-farm). Besides, local food products issues from initiatives may reconnect providers and consumers, revaluing local food products. However, is necessary the institutional and organizational involvement to encourage the initiatives. Furthermore, to promote touristic places, by an integrated rural tourism approach it may involve all stakeholders to promote local products and issues from initiatives. Indirectly it may create local employs.